An evaluation of patient outcomes following transcatheter pulmonary valve implantation: a meta-analysis. (14th October 2021) - Saluja, S; Contractor, H; Wiltshire, R; Mannan, F; Hussain, N; Abidin, N; Tin, L; Ali, S; Saluja, S; Khan, K; Sobolewska, J; Sood, P; et al.
Abstract: Background: Transcatheter pulmonary valve implantation has emerged as an effective alternative to surgery in patients with congenital Right Ventricular Outflow Tract Dysfunction (RVOT). There is demonstrable evidence that Percutaneous Pulmonary Valve Implantation (PPVI) effectively restores conduit graft viability with a consequent improvement in right ventricular pressures. Aim: The objective of this study was to perform a meta-analysis of all previously published studies examining the outcome of PPVI and the associated early and late peri-procedural factors in patients with RVOT dysfunction. Data from procedures performed within our own centre have also been included. Methodology: We performed a meta-analysis of all observational studies investigating early and late outcomes following PPVI. Risk ratios and risk differences were pooled in a random-effects model. The I 2 statistic was used to quantify heterogeneity between studies. We searched EMBASE, MEDLINE, CINAHL, PsychInfo and Cochrane databases from their inception until 2021. Studies were included if they reported any comparative data regarding study endpoints. Primary endpoint was mean RVOT gradient. Secondary end points include pulmonary regurgitation fraction, left and right ventricular end-diastolic and systolic volume indexes, and left ventricular ejection fraction. Complication rates were considered a safety endpoint. Results: A total of 23 studies with 1501 participants enrolled were included in the final meta-analysis. The RVOT gradient decreased significantly [weighted mean difference (WMD) = −20.32 mmHg; 95% confidence interval (CI): −22.15, −19.11; p<0.001]. Mean right ventricular (RV) systolic pressures fell significantly [(WMD)= −18.4 mmHg; 95% CI: −16.4, −20.2; p<0.001) and RV diastolic pressures decreased significantly [(WMD) = −6.3 mmHg, 95% CI: −4.3, −8.9; p<0.001). Pulmonary regurgitation fraction (PRF) also decreased notably (WMD = −24.38%, 95% CI: −28.27, −17.32; p<0.001).The incidence of infective endocarditis was 1.8% (95% CI: 0.7–3.8). Conclusion: PPVI is an effective and safe strategy in relieving right ventricular remodelling and improving haemodynamic and clinical outcomes in patients with RVOT dysfunction. Multi-centre collaborations are essential to further determine the long-term effects of PPVI on cardiac function, exercise tolerance and quality of life in RVOT dysfunction. Funding Acknowledgement: Type of funding sources: None.